Identifying potential DNA methylation markers for the detection of esophageal cancer in plasma - Pei, Bing; Zhao, Guodong; Geng, Zhixin; Wang, Yue; Wang, Menglin; Wang, Xiaomei; Xiong, Shangmin; Zheng, Minxue (Frontiers in Genetics, 2023)
Background: Esophageal cancer (EC) is a leading cause of cancer-related death in China, and the five-year survival rate for EC was less than 30% because most cases were diagnosed and treated at advanced stage. However, there is still a lack of low-cost, efficient, and accurate non-invasive methods for the early detection of EC at present. Method: Forty-eight EC plasma and 101 control plasma samples in training cohort were collected From January 1, 2021 to December 31, 2021, and seven cancer-related DNA methylation makers (ELMO1, ZNF582, FAM19A4, PAX1, C13orf18, JAM3 and TERT) were tested in these samples to select potential markers. Twenty EC, 10 gastric cancer (GC), 10 colorectal cancer (CRC) and 20 control plasma samples were collected in a validation cohort to evaluate the 2-gene panel. Results: ZNF582, FAM19A4, JAM3 or TERT methylation in plasma was shown to significantly distinguish EC and control subjects (p<0.05), and the combination of ZNF582 and FAM19A4 methylation was the 2-gene panel that exhibited the best performance for EC detection with 60.4% sensitivity (95% CI: 45.3 – 73.9%) and 83.2% specificity (95% CI: 74.1 – 89.6%) in the training cohort. The performance of this 2-gene panel showed no significant difference between different age and gender groups. When the 2-gene panel was combined with CEA, the sensitivity for EC detection of was further improved to 71.1%. In validation cohort, the sensitivity of the 2-gene panel for detecting EC, GC, and CRC was 60.0%, 30.0%, and 30.0%, respectively, with a specificity of 90.0%. Conclusion: The identified methylation marker panel provided a potential non-invasive strategy for EC detection, but further validation should be performed in more clinical centers.